Altered Cellular and Humoral Immunity to Varicella‐Zoster Virus in Patients With Autoimmune Diseases. Issue 11 (November 2014) - Rondaan, Christien; de Haan, Aalzen; Horst, Gerda; Hempel, J. Cordelia; van Leer, Coretta; Bos, Nicolaas A.; van Assen, Sander; Bijl, Marc; Westra, Johanna
<x xml:space="preserve">Abstract</x> Objective Patients with autoimmune diseases such as systemic lupus erythematosus (SLE) and granulomatosis with polyangiitis (Wegener's) (GPA) have a 3–20‐fold increased risk of herpes zoster compared to the general population. The aim of this study was to evaluate if susceptibility is due to decreased levels of cellular and/or humoral immunity to the varicella‐zoster virus (VZV). Methods A cross‐sectional study of VZV‐specific immunity was performed in 38 SLE patients, 33 GPA patients, and 51 healthy controls. Levels of IgG and IgM antibodies to VZV were measured using an in‐house glycoprotein enzyme‐linked immunosorbent assay (ELISA). Cellular responses to VZV were determined by interferon‐γ (IFNγ) enzyme‐linked immunospot (ELISpot) assay and carboxyfluorescein succinimidyl ester (CFSE) dye dilution proliferation assay. Results Levels of IgG antibodies to VZV were increased in SLE patients as compared to healthy controls, but levels of IgM antibodies to VZV were not. Antibody levels in GPA patients did not differ significantly from levels in healthy controls. In response to stimulation with VZV, decreased numbers of IFNγ spot‐forming cells were found among SLE patients (although not GPA patients) as compared to healthy controls. Proliferation of CD4+ T cells in response to stimulation with VZV was decreased in SLE patients but not GPA patients. Conclusion SLE patients have increased levels of IgG antibodies against VZV, while cellular immunity is decreased. In GPA patients, antibody levels as well as cellular responses to VZV were comparable to those in healthy controls. These data suggest that increased prevalence of herpes zoster in SLE patients is due to a poor cellular response. Vaccination strategies should aim to boost cellular immunity against VZV.